2019
DOI: 10.1371/journal.pone.0221809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PEPFAR funding policy change on HIV service delivery in a large HIV care and treatment network in Nigeria

Abstract: The transition to PEPFAR 2.0 with its focus on country ownership was accompanied by substantial funding cuts. We describe the impact of this transition on HIV care in a large network of HIV clinics in Nigeria. We surveyed 30 comprehensive HIV treatment clinics to assess services supported before (October 2013-September 2014) and after (October 2014-September 2015) the PEPFAR funding policy change, the impact of these policy changes on service delivery areas, and response of clinics to the change. We compared d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 26 publications
3
30
0
Order By: Relevance
“…Some programs have instituted protections to limit the burden of out-of-pocket expenses imposed by charging user fees [36]. NIMR (our study site), for example, instituted fee exemptions for children, pregnant women, elderly and indigent patients.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Some programs have instituted protections to limit the burden of out-of-pocket expenses imposed by charging user fees [36]. NIMR (our study site), for example, instituted fee exemptions for children, pregnant women, elderly and indigent patients.…”
Section: Plos Onementioning
confidence: 99%
“…Similar user fee-based strategies have been implemented in other countries the region, and particularly in Western Africa, to cover the cost of lab monitoring tests, hospital registration clinical consultations, as well as to compensate for low provider wages [40]. Mean yearly fees vary widely depending on context, average around $40 USD yearly, and range from as low as $4 USD to as much as $166 USD [36,40]. There is a global challenge to dramatically decrease the cost of ART care and data such as these can help drive the urgency of this challenge.…”
Section: Plos Onementioning
confidence: 99%
“…al., reported on group psychotherapy for depression integrated into HIV treatment (38). Some of the structures identi ed in our study and those utilized in Malawi, Zimbabwe and Uganda are already connected to HIV services infrastructure, and are very widely spread across Nigeria both in rural and urban settings (39,40).…”
Section: Discussionmentioning
confidence: 91%
“…In Zimbabwe, Duffy et al described a stepped-care model integrating mental health screening and referral to treatment [37] and in Uganda, Mpungu et al, reported on group psychotherapy for depression integrated into HIV treatment [38]. Some of the structures identified in our study and those utilized in Malawi, Zimbabwe and Uganda are already connected to HIV services infrastructure, and are very widely spread across Nigeria both in rural and urban settings [39,40]. Four themes were identified relating to challenges and barriers to integration; (the double burden of HIV and mental health stigma and the problems of early detection, existing health policy gaps and structural challenges, poor human resources for mental health care in Nigeria and dearth of research for data and action).…”
Section: Discussionmentioning
confidence: 91%